Teddy helps: caring & sharing - Krutop, Lee (Five Mile Pr Pty Ltd Australia, 2008)
"Teddy Helps" is a heartwarming story about Teddy the bear, who loves to lend a helping hand to his friends. Whether it's assisting a lost bunny find its way home or helping a bird build its nest, Teddy shows the importance of kindness and teamwork. Through his thoughtful actions, he teaches young readers the value of compassion and the joy of helping others in their community.